INTEGRASI SOSIAL–KULTURAL DALAM ARSIP DIGITAL DI KLAB AMATIR FOTO - Regina Octavia Ronald; Nanang Ganda Prawira; Zakaria Sukarya Soeteja; Tri Karyono; Rahmadi - (Institut Seni Indonesia Yogyakarta, 2026)
The digital transformation of recorded media art has created new opportunities for photo communities to adapt while preserving their cultural values. This article examines how the Bandung Amateur Photo Association, Perhimpunan Amatir Foto Bandung (PAF), develops digital archiving practices that integrate social, cultural, and educational functions within a socio-cultural framework. Using a qualitative case study approach, data were collected through participant observation, in-depth interviews, and analysis of physical and digital archives. The findings reveal that PAF’s digital archive functions not only as a repository of photographic works, but also as a space for visual cultural interaction where photographic traditions, collective ethics, and digital technologies continuously negotiate. The archive also serves as a medium for non-formal photography learning by connecting different generations through practices of sharing, curating, and reflecting on photographic works. The socio-cultural integration highlighted in this study demonstrates how digital media extends community-based cultural practices that have evolved alongside PAF’s development. This article contributes to recorded media art studies by positioning digital archival practices as participatory and collaborative forms of visual cultural inheritance rooted in community culture.